Розвиток історичної бібліографії Криму - Назарчук, Т. (Національна бібліотека України ім.В.І.Вернадського, 2007)
Biography and creative activity of one of leading bibliographers the Crimea of 1920th – V. V. Simonovskiy is examined in the article. He was the active propagandist of bibliographic science and study of a particular region, and he made considerable contribution to systematization of the published legacy on history and ethnography of Crimean peoples.